A battery silicon negative electrode, preparation method, sulfide all-solid-state lithium battery and application
By using a silicon negative electrode covered with a mixture of B, O, Li, and C in a sulfide all-solid state battery, the problem of unstable metal lithium negative electrode and sulfide solid electrolyte is solved, the rate performance and long cycle stability of the battery are improved, and it is suitable for the commercial promotion of sulfide all-solid state batteries.
Patent Information
- Application Number
- CN202210793959.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-07-07
AI Technical Summary
In sulfide all-solid state batteries, the metal lithium anode and the sulfide solid electrolyte are unstable, which easily leads to short-circuiting of the battery. Both high-voltage anode materials and low-voltage and low-capacity anode materials have problems with low energy density.
A silicon negative electrode covered with a mixture composed of B, O, Li, and C is coated with a nano-Li-C-B-O mixture on the surface of the nano-silicon negative electrode by a vapor phase method to form a dense and high lithium ion conductivity coating layer.
The rate performance and long cycle stability of Si negative electrodes in sulfide all-solid state batteries are improved, and are suitable for the commercial promotion of Si negative electrodes in sulfide all-solid state batteries.
Smart Images

Figure CN115172669B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of batteries, and in particular to a battery silicon negative electrode, a preparation method, a lithium battery and applications. Background Art
[0002] At present, sulfide solid electrolytes have received widespread attention due to their high ionic conductivity. The high-energy-density all-solid-state battery composed of sulfide solid electrolytes and high-capacity metal lithium anodes (~3870mAh g-1) has become the mainstream development direction in the future. However, the use of metal lithium anodes currently has problems such as instability with sulfide solid electrolytes and easy battery short circuits.
[0003] In order to solve the above problems, the current related technologies mainly avoid the use of metal lithium negative electrodes and use some high-voltage negative electrode materials, such as metal In and lithium titanate negative electrodes, or use some low-voltage and low-capacity negative electrodes, such as graphite. However, the use of In or lithium titanate negative electrodes has the problem of high voltage platform, which will further reduce the specific capacity of the whole battery and restrict the overall energy density of the battery; graphite negative electrodes will also cause similar negative effects.
[0004] In addition to the above operations, there are also related technologies that use high-capacity Si negative electrodes to increase the energy density of the negative electrode side of the battery cell, thereby increasing the energy density of the overall battery. However, there are many problems with Si negative electrodes in sulfide all-solid-state batteries: on the one hand, the lithium ion conductivity of pure Si itself is low, resulting in poor rate performance of Si negative electrodes; on the other hand, the electronegativity of Si and S inside the sulfide solid electrolyte is different, which easily leads to the formation of a Li+ space charge layer at the interface between the electrolyte and Si, which hinders the rapid transmission of lithium ions and further affects the rate performance of the silicon negative electrode. Summary of the invention
[0005] The present disclosure provides a battery silicon negative electrode, a preparation method, a lithium battery and an application, which can solve one or more technical problems mentioned in the background technology. To solve the above technical problems, the present disclosure provides the following technical solutions:
[0006] As one aspect of an embodiment of the present disclosure, a battery silicon negative electrode is provided, comprising: a silicon negative electrode coated with a mixture of B, O, Li, and C.
[0007] Optionally, the mixture includes Li 3-x C x B 1-x O 3 , where x is between 0.1 and 0.5.
[0008] Optionally, the silicon negative electrode is a silicon ball or a silicon rod.
[0009] Optionally, the mixture further comprises Li 3 BO 3 and / or LiBO 2 ;
[0010] And / or, the mixture is prepared by a gas phase method.
[0011] Optionally, the silicon negative electrode is a silicon sphere, and the diameter of the silicon sphere is 100-500nm.
[0012] As another aspect of the embodiments of the present disclosure, a method for preparing a silicon negative electrode for a battery is provided, comprising the following steps:
[0013] The lithium compound is placed in the first temperature control zone of the constant temperature reaction container, the boride is placed in the second temperature control zone of the constant temperature reaction container, and the silicon ball or silicon rod is placed in the third temperature control zone of the constant temperature reaction container;
[0014] Inert gas is introduced into the constant temperature reaction container, and different temperatures are applied to the first temperature control zone, the second temperature control zone, and the third temperature control zone, respectively, so that the lithium compound and the boride are coated on the surface of the silicon ball or the silicon rod in the gas phase;
[0015] Switch the inert gas to oxygen and pass it into the constant temperature reaction container, set the temperature of the third temperature control zone to 200-400° C., so that the lithium compound and boride on the surface of the silicon ball or silicon rod are oxidized into a Li-BO coating layer;
[0016] The oxygen is switched to carbon dioxide gas and introduced into the constant temperature reaction container, and the temperature of the third temperature control zone is set to 400-800° C., so that the Li-BO coating layer is transformed into a Li-BCO coating layer.
[0017] Optionally, the Li-BCO coating layer has a thickness of 2-50 nm;
[0018] And / or, the boride comprises one or more of the following materials: boron ethoxide, boron isopropoxide, boron trichloride, boron tribromide or boron iodide;
[0019] And / or, the lithium compound includes one or more of the following materials: lithium ethoxide, lithium isopropoxide, lithium amide or lithium imide.
[0020] As another aspect of an embodiment of the present disclosure, a sulfide all-solid-state lithium battery is provided, comprising the above-mentioned battery silicon negative electrode.
[0021] Optionally, the sulfide all-solid-state lithium battery also includes a positive electrode material, and the positive electrode material is one or more of the following materials: a Li-Fe-PO based positive electrode, a Li-Ni-Mn-Co-O based positive electrode or a S positive electrode.
[0022] As another aspect of an embodiment of the present disclosure, an application of the above-mentioned battery silicon negative electrode is provided, and the battery silicon negative electrode is used in a polymer all-solid-state battery, an oxide all-solid-state battery or a halide all-solid-state battery.
[0023] The beneficial effects of the present disclosure are: by using a gas phase method to coat a layer of nano-Li-CBO mixture on the surface of a traditional nano-silicon negative electrode, the coating layer has the characteristics of high lithium ion conductivity, uniformity, density, high lithium ion conductivity, low potential stability, etc. It can improve the rate performance and long cycle stability of the Si negative electrode in the sulfide all-solid-state battery. It is suitable for the commercial promotion of the Si negative electrode in the sulfide all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the method for preparing the battery silicon negative electrode in Example 1 is shown. DETAILED DESCRIPTION
[0025] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0026] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0027] The particle size of the following sulfide electrolytes can be processed by a ball mill, a sand mill or a jet mill. The constant temperature reaction vessel can be a muffle furnace, an oil bath pot or a constant temperature reaction vessel. An inert container refers to a container filled with an inert gas (nitrogen or argon, etc.) to exclude other gases.
[0028] Example 1
[0029] Please see attached Figure 1 , a method for preparing a Li-BCO coated battery silicon negative electrode comprises the following steps:
[0030] Take 0.2g lithium ethanol and place it in the temperature control zone on the left side of the tube furnace, 1g boron iodide and place it in the temperature control zone in the middle of the tube furnace, and 10g nano silicon balls and place it in the temperature control zone on the right side of the tube furnace. High-purity argon protective gas is introduced with a gas flow rate of 0.2L / min; the temperature zones from left to right are set at 80℃, 350℃, and 25℃, respectively, and the reaction time is 1h, and then the high-purity argon is switched to oxygen with a gas flow rate of 0.2L / min; the temperature on the right side of the nano silicon ball is set to 300℃, and the reaction time is 3h to obtain a nano silicon negative electrode (Li-BO@Si) coated with a Li-BO nano layer. Continue to switch oxygen to carbon dioxide gas with a gas flow rate of 0.2L / min; the temperature on the right side of the nano silicon ball is set to 600℃, and the reaction time is 3h, and the Li-BO nano coating layer is converted into a Li-BCO nano coating layer, and a nano silicon negative electrode (Li-BCO@Si) coated with a Li-BO nano layer is obtained.
[0031] Weigh LiNbO according to the mass ratio of 70:27:3 3 Coated NCM811, Li 6 PS 5 Cl solid electrolyte and VGCF conductive carbon were ground for 10 min to prepare a composite positive electrode. 30 mg of the composite positive electrode and 120 mg of the sulfide solid electrolyte were pressed into a positive electrode and electrolyte layer mixed assembly with a diameter of 10 mm.
[0032] The prepared Li-BCO@Si mixed negative electrode material and Li 6 PS 5 Cl solid electrolyte, grind for 10min to prepare sulfide composite negative electrode. 3mg composite negative electrode was pressed on the above positive electrode and electrolyte layer assembly, assembled all-solid-state battery and tested for electrochemical performance. Test conditions are: current rate switching between 0.1C-0.3C-0.5C-1C-2C, voltage range 3.0~4.3V (vs.Li+ / Li), test pressure 1MPa, cycle 1, 100, 300 weeks, test comparison results are shown in Table 1. At the same time, the negative electrode materials were tested using untreated Si nanoparticles and Li-BCO monomer materials as comparative data.
[0033] It can be seen from Table 1 that compared with using untreated Si anode and Li-BCO monomer material as the anode, the use of Li-BCO@Si has a significant improvement in rate performance, while the Li-BCO monomer material has no obvious lithium insertion capacity.
[0034] Table 1
[0035]
[0036] Ps: -- means the battery cannot work properly and a short circuit occurs
[0037] As another aspect of the embodiments of the present disclosure, a battery silicon negative electrode is obtained by the above-mentioned preparation method, including: a silicon negative electrode coated with a mixture of B, O, Li, and C.
[0038] In some embodiments, the mixture of B, O, Li, and C includes Li 3-x C x B 1-x O 3 , where x is 0.1-0.5, for example, including Li 2.9 C 0.1 B 0.9 O 3 , Li 2.8 C 0.2 B 0.8 O 3 , Li 2.7 C 0.3 B 0.7 O 3 , Li 2.6 C 0.4 B 0.6 O 3 , Li 2.5 C 0.5 B 0.5 O 3 , or one or more of the following.
[0039] In some embodiments, the mixture further comprises one or more of the following materials: Li 3 BO 3 or LiBO 2 For example, a mixture including Li 2.9 C 0.1 B 0.9 O 3 , Li 2.8 C 0.2 B 0.8 O 3 , Li 3 BO 3 and LiBO 2 These substances, or mixtures including Li 2.8 C 0.2 B 0.8 O 3 , Li 2.7 C 0.3 B 0.7 O 3 , Li 2.6 C 0.4 B 0.6 O 3 , Li3 BO 3 and LiBO 2 These substances, or mixtures including Li 2.9 C 0.1 B 0.9 O 3 , Li 2.8 C 0.2 B 0.8 O 3 , Li 2.7 C 0.3 B 0.7 O 3 , Li 2.6 C 0.4 B 0.6 O 3 , Li 2.5 C 0.5 B 0.5 O 3 , Li 3 BO 3 and LiBO 2 , or, a mixture including Li 2.5 C 0.5 B 0.5 O 3 、LiBO 3 Those skilled in the art will appreciate that the combination of the mixture is not limited to the combination of the above materials, which is just an example of different combinations.
[0040] In some embodiments, the nano silicon balls in the above embodiments may be replaced with silicon rods to obtain silicon rod negative electrode materials.
[0041] In some embodiments, the lithium ethoxide in the above embodiments can be replaced by a corresponding mass of lithium isopropoxide. Similarly, the boron iodide can be replaced by a corresponding mass of boron trichloride or boron tribromide.
[0042] In some embodiments, the diameter of the silicon sphere ranges from 100 to 500 nm. For example, the diameter of the silicon sphere may be 100 nm, 250 nm, or 500 nm. The diameter of the silicon sphere may be adjusted as needed.
[0043] As another aspect of the embodiments of the present disclosure, a sulfide all-solid-state lithium battery is also provided, wherein the sulfide all-solid-state lithium battery includes the battery silicon negative electrode in the above embodiment.
[0044] In some embodiments, the lithium battery further includes a positive electrode material. For example, the positive electrode material may be a Li-Fe-PO-based positive electrode, a Li-Ni-Mn-Co-O-based positive electrode, or a S positive electrode.
[0045] As another aspect of the embodiments of the present disclosure, an application of a battery silicon negative electrode is provided, for example, applying it to a polymer all-solid-state battery, an oxide all-solid-state battery, or a halide all-solid-state battery.
[0046] Example 2
[0047] As one aspect of this embodiment, this embodiment provides a method for preparing a Li-BCO coated battery silicon negative electrode, comprising the following steps:
[0048] Take 0.3g of lithium amide or lithium imide and place it in the temperature control zone on the left side of the tube furnace, 1g of ethanol boron or isopropanol boron and place it in the temperature control zone in the middle of the tube furnace, and 10g of nano silicon balls or silicon rods and place them in the temperature control zone on the right side of the tube furnace. High-purity argon protective gas is introduced with a gas flow rate of 0.2L / min; the temperature zones from left to right are set at 450℃, 250℃, and 25℃, respectively, and the reaction time is 1h, then the high-purity argon is switched to oxygen with a gas flow rate of 0.2L / min; the temperature on the right side of the nano silicon ball is set to 200℃, and the reaction time is 3h to obtain a nano silicon negative electrode (Li-BO@Si) coated with a Li-BO nano layer. Continue to switch oxygen to carbon dioxide gas with a gas flow rate of 0.2L / min; the temperature on the right side of the nano silicon ball is set to 400℃, and the reaction time is 3h, and the Li-BO nano coating layer is converted into a Li-BCO nano coating layer, and a nano silicon negative electrode (Li-BCO@Si) coated with a Li-BO nano layer is obtained.
[0049] Weigh LiNbO according to the mass ratio of 70:27:3 3 Coated NCM811, Li 6 PS 5 Cl solid electrolyte and VGCF conductive carbon were ground for 10 min to prepare a composite positive electrode. 30 mg of the composite positive electrode and 120 mg of the sulfide solid electrolyte were pressed into a mixed assembly of a positive electrode and an electrolyte layer with a diameter of 10 mm.
[0050] The prepared Li-BCO@Si mixed negative electrode material and Li 6 PS 5 Cl solid electrolyte, grind for 10min to prepare sulfide composite negative electrode. 3mg composite negative electrode was pressed on the above positive electrode and electrolyte layer assembly, assembled all-solid-state battery and electrochemical performance tested. Test conditions are: current rate switching between 0.1C-0.3C-0.5C-1C-2C, voltage range 3.0~4.3V (vs.Li+ / Li), test pressure 1MPa, cycle 1, 100, 300 weeks, test comparison results are shown in Table 2.
[0051] Table 2
[0052]
[0053] As another aspect of the embodiments of the present disclosure, a sulfide all-solid-state lithium battery is also provided, wherein the sulfide all-solid-state lithium battery includes the battery silicon negative electrode in this embodiment.
[0054] In some embodiments, the sulfide all-solid-state lithium battery also includes a positive electrode material. For example, the positive electrode material can be a Li-Fe-PO-based positive electrode, a Li-Ni-Mn-Co-O-based positive electrode, or a S positive electrode.
[0055] As another aspect of this embodiment, an application of a battery silicon negative electrode is also provided, for example, it is applied to polymer all-solid-state batteries, oxide all-solid-state batteries, and halide all-solid-state batteries.
[0056] Example 3
[0057] As one aspect of this embodiment, this embodiment provides a method for preparing a Li-BCO coated battery silicon negative electrode, comprising the following steps:
[0058] Take 0.3g lithium ethoxide and / or lithium isopropoxide and place it in the left temperature control zone of the tube furnace, 1g of one of boron trichloride, boron tribromide or boron iodide or a combination of the three is placed in the middle temperature control zone of the tube furnace, and 10g of nano silicon balls or silicon rods is placed in the right temperature control zone of the tube furnace. High-purity argon protective gas is introduced with a gas flow rate of 0.2L / min; the temperature zones from left to right are set at 100℃, 200℃, and 25℃, respectively, and the reaction time is 1h, then the high-purity argon is switched to oxygen with a gas flow rate of 0.2L / min; the temperature on the right nano silicon ball side is set to 400℃, and the reaction time is 3h, to obtain a nano silicon negative electrode (Li-BO@Si) coated with a Li-BO nano layer. Continue to switch oxygen to carbon dioxide gas with a gas flow rate of 0.2 L / min; set the temperature of the right nanosilicon ball side to 800°C until the Li-BO nanocoating layer is transformed into a Li-BCO nanocoating layer to obtain a nanosilicon negative electrode (Li-BCO@Si) coated with a Li-BO nanolayer.
[0059] Weigh LiNbO according to the mass ratio of 70:27:3 3 Coated NCM materials (such as NCM811), Li 6 PS 5 Cl solid electrolyte and VGCF conductive carbon were ground for 10 min to prepare a composite positive electrode. 30 mg of the composite positive electrode and 120 mg of the sulfide solid electrolyte were pressed into a positive electrode and electrolyte layer mixed assembly with a diameter of 10 mm.
[0060] The prepared Li-BCO@Si mixed negative electrode material and Li6 PS 5 Cl solid electrolyte, grind for 10min to prepare sulfide composite negative electrode. 3mg composite negative electrode was pressed on the above positive electrode and electrolyte layer assembly, assembled all-solid-state battery and electrochemical performance tested. Test conditions are: current rate switching between 0.1C-0.3C-0.5C-1C-2C, voltage range 3.0~4.3V (vs.Li+ / Li), test pressure 1MPa, cycle 1, 100, 300 weeks, test comparison results are shown in Table 3.
[0061] Table 3
[0062]
[0063] In some embodiments, lithium ethoxide and / or lithium isopropoxide may also be replaced by a combination of other lithium compounds, such as a combination of lithium ethoxide, lithium isopropoxide, lithium amide, or lithium imide.
[0064] In some embodiments, boron trichloride, boron tribromide or boron iodide may also be replaced by a combination of other borides, such as a combination of boron ethoxide, boron isopropoxide, boron trichloride, boron tribromide or boron iodide.
[0065] As another aspect of the embodiments of the present disclosure, a sulfide all-solid-state lithium battery is also provided, wherein the sulfide all-solid-state lithium battery includes the battery silicon negative electrode in this embodiment.
[0066] In some embodiments, the sulfide all-solid-state lithium battery also includes a positive electrode material. For example, the positive electrode material can be a Li-Fe-PO-based positive electrode, a Li-Ni-Mn-Co-O-based positive electrode, or a S positive electrode.
[0067] As another aspect of this embodiment, an application of a battery silicon negative electrode is also provided, for example, it is applied to polymer all-solid-state batteries, oxide all-solid-state batteries, and halide all-solid-state batteries.
[0068] Although embodiments of the present disclosure have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present disclosure, and the scope of the present disclosure is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a silicon negative electrode for a battery, characterized in that: The steps include: The lithium compound is placed in the first temperature control zone of the constant temperature reaction container, the boride is placed in the second temperature control zone of the constant temperature reaction container, and the silicon ball or silicon rod is placed in the third temperature control zone of the constant temperature reaction container; Inert gas is introduced into the constant temperature reaction container, and different temperatures are applied to the first temperature control zone, the second temperature control zone, and the third temperature control zone, respectively, so that the lithium compound and the boride are coated on the surface of the silicon ball or the silicon rod in the gas phase; Switch the inert gas to oxygen and pass it into the constant temperature reaction container, set the temperature of the third temperature control zone to 200-400° C., so that the lithium compound and boride on the surface of the silicon ball or silicon rod are oxidized into a Li-BO coating layer; Switch oxygen to carbon dioxide gas and introduce it into the constant temperature reaction container, set the temperature of the third temperature control zone to 400-800° C., so that the Li-BO coating layer is transformed into the Li-BCO coating layer; The Li-BCO coating layer includes LiC x B 1-x O 3, Here, the value of x is 0.1-0.
5.
2. The method for preparing a battery silicon negative electrode according to claim 1, characterized in that: The thickness of the Li-BCO coating layer is 2-50 nm.
3. The method for preparing a silicon negative electrode for a battery according to claim 1, characterized in that: The boride includes one or more of the following materials: boron ethoxide, boron isopropoxide, boron trichloride, boron tribromide or boron iodide.
4. The method for preparing a silicon negative electrode for a battery according to claim 1, characterized in that: The lithium compound includes one or more of the following materials: lithium ethoxide, lithium isopropoxide, lithium amide or lithium imide.
5. A lithium battery, comprising a battery silicon negative electrode prepared by the method for preparing a battery silicon negative electrode according to any one of claims 1 to 4.
6. The lithium battery according to claim 5, characterized in that The lithium battery also includes a positive electrode material, which is one or more of the following materials: a Li-Fe-PO-based positive electrode, a Li-Ni-Mn-Co-O-based positive electrode, or a S positive electrode.
7. An application of a battery silicon negative electrode prepared by the battery silicon negative electrode preparation method as described in any one of claims 1 to 4, wherein the battery silicon negative electrode is used in a polymer all-solid-state battery, an oxide all-solid-state battery, a sulfide all-solid-state battery or a halide all-solid-state battery.
Citation Information
Patent Citations
Nano silicon composite material with core-shell structure and preparation method thereof
CN111883759A
Metal boroxate modified lithium ion battery electrode composite material and preparation method thereof
CN112864357A
Cited By
Silicon-based material with self-adaptive coating layer, preparation method of silicon-based material and lithium battery
CN121983541A